Implementation of Project-Based Learning to Enhance Activeness and Statistics Learning - Rafianti Bau, Siti; Napitupulu, Bettisari; Kho, Ronaldo (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
This study examines the effectiveness of the Project-Based Learning model in improving students’ activeness and learning outcomes in the Statistics subject at SMK Negeri 3 Kesehatan dan Pekerjaan Sosial Mimika. The research was conducted to determine how far this learning model can foster active participation and enhance students’ understanding through meaningful learning experiences. The main objective is to create a dynamic learning atmosphere where students are directly involved in exploring, designing, and presenting projects related to statistical concepts. The study applied a quantitative approach using a Classroom Action Research design consisting of planning, action, observation, and reflection stages. Data collection utilized observation sheets, project rubrics, and achievement tests. The findings indicated that students became more engaged during the learning process, showing greater initiative and collaboration in completing project tasks. Learning outcomes also demonstrated noticeable improvement, with students achieving higher levels of comprehension and problem-solving ability. Moreover, the project results reflected students’ creativity and ability to apply statistical concepts in practical contexts. Overall, the implementation of the Project-Based Learning model succeeded in promoting an active, participatory, and student-centered classroom environment, supporting both cognitive and affective learning growth among students.